HUBUNGAN KETERSEDIAAN SANITASI DASAR TERHADAP STUNTING DI DESA SALO TIMUR KECAMATAN SALO TAHUN 2025 - SRI HARDIANTI; Widia Ardila (Universitas Pahlawan Tuanku Tabusai, 2025)
Stunting is a public health problem associated with increased risk of illness, death, and stunted growth, both motoric (developmental) and mental. One of the causes of stunting in children can be influenced by several factors such as basic hygiene, food preparation, and maternal nutritional knowledge about children. The purpose of the study was to analyze the relationship between the availability of basic sanitation and stunting in East Salo Village, Salo District in 2025. The type of research is an analytical observational study with a cross-sectional design. The study was conducted on April 6-15, 2025 with a sample of 67 respondents who experienced stunting and did not experience stunting using the total sampling technique. Data collection using a questionnaire. Data analysis used univariate and bivariate analysis with the Chi Square test. The results of the univariate analysis obtained 38 respondents (56.7%) had unhealthy basic sanitation, 36 respondents (53.7%) mothers had less knowledge about nutrition and 32 toddlers (47.8) toddlers experienced stunting. The results of the Chi Square test showed a significant relationship between basic sanitation and Stunting in Salo Timur Village, Salo District in 2025, namely the results of basic sanitation statistics with a p value = 0.002 and maternal nutritional knowledge with a p value = 0.000. The conclusion is that the incidence of Stunting is directly influenced by the independent variable of basic sanitation which indirectly influences Stunting through a history of infectious diseases. Respondents are expected to always pay attention to the nutritional status of toddlers by bringing toddlers to the integrated health post every month to be weighed (BB) and height (TB) and given vitamin A to toddlers.